The effects of financial and non-financial incentives on the demand for a sustainable DRT system - Aljoscha Minnich; Holger A. Rau; Jan Schlüter (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2020)
This paper analyzes in a large-scale field experiment (N = 2,980) the incentive effects of monetary vs. non-monetary incentives on the usage of a sustainable Demand Responsive Transport (DRT) system. Financial incentives were implemented by offering customers vouchers, which were received when they reached a certain threshold of rides with the DRT service (EcoBus). In the non-financial incentive treatment, we applied the same thresholds. In this case, we exploited the sustainable character of the EcoBus and offered environmental certificates which documented the saved level of carbon dioxide because of the bus usage. The data show strong support that financial incentives excellently work to increase the demand for a sustainable transport service. EcoBus rides nearly doubled during the intervention phase. Interestingly, non-financial incentives also have a positive effect on the demand for the bus service. However, the effect is attenuated at the end of the treatment phase. Thus, financial incentives outperform non-financial incentives.
Keywords: C93; D12; D83; D91; 330; Demand Responsive Transport; Field Experiment; Incentive Effects